Transition in Early Childhood Education - Musfita, Regita; Setiasih, Ocih (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purpose of this article is to explain why the transition must be researched, comprehended, and included in the Early Childhood Education (ECE) level. In the early childhood education, we need to perceive that involvement, collaboration, and communication between children, families, schools, and community are important factors that will strengthen the transition towards a positive direction in helping children to go to school and encourage them in passing through the transition to Elementary School. Fundamentally a child's growth is influenced by child development aspects which include religious, moral values, physical and motor, cognitive, social-emotional, language and art that has become the basis of every development in learning programs that will be carried out at the level of Early Childhood and Elementary Education. By applying the literature review method, this article aims to gain a holistic apprehension from various perspectives on the significance of transition in Early Childhood Education. The aim of the transition in Early Childhood Education is none other than to help children develop the basic potential that has already existed inside them, not only for increasing children's knowledge and independence but also their apprehension which will later support each other in preparing themselves for Primary level